Turnover Premium, Foreign Institutional Ownership, and Time-Varying Risk Premium in Taiwan Equity Markets - Chen, Ying-Jen; Lee, Jen-Sin (Journal of Reviews on Global Economics, 2015)
The low turnover premium found in U.S. equity markets is also found in Taiwan market, unlike the mixed evidence for other stylized effects such as size, book-to-market ratio and momentum. Consistent with investor overconfidence hypothesis proposed by Odean (1998, 1999), the percentage of foreign institutional shareholdings in a stock is found to vary inversely with turnover premium. This inverse relation is robust to the influence of other forces that may interact with turnover rate, such as market capitalization, book-to-market ratio and 6-month past returns, respectively. Time-varying risk premium, particularly in low turnover-low foreign institutional shareholdings percentage portfolio, provides partial explanation for the phenomenon, but the inverse relation persists after risk adjustment by models such as unconditional CAPM, Fama-French three factor model and conditional CAPM.